IMPLEMENTASI KOMUNIKASI TERPADU UNTUK PERUBAHAN SOSIAL PADA KOPERASI TANI MANDIRI SEJAHTERA (TAMARA) DALAM PENYEBARAN INOVASI TEKNOLOGI PERTANIAN - Avief, Dendi Noor; Nuraprilia, Hana; Kamelia, Innayach; Taufik, Muhammad Wildan; Chalisa, Vadia Lubna (Agripreneur : Jurnal Pertanian Agribisnis, 2025)
This study examines the implementation of integrated communication for social change in the process of adopting and disseminating agricultural technology innovations at the TAMARA Cooperative in Sukabumi. This study uses a qualitative approach with Figueroa's integrated communication theory as the framework for analysis. Data was collected through in-depth interviews with the founders and members of the cooperative. The results of the study show that the adoption of technologies such as portable soil testing equipment, tractors, processing machines, and packaging machines was carried out through a process of dialogue, consensus, collective action, and participatory evaluation. The source of the technology came from a grant from Bank Indonesia, which was tailored to the needs of the members. Technological innovations have proven to increase work efficiency, product quality and durability, and encourage changes in farmers' behavior and knowledge. The main challenges faced are the education process, technology adaptation, and product quality assurance. These findings are influenced by Sukabumi's strong local character of community solidarity, so replication in other areas requires adjustments to the social context. The cooperative addresses differences in technological literacy through gradual training and hands-on mentoring so that all members can adapt. Sustainability strategies for the next 3–5 years include plans to build greenhouses, expand precision technology, and diversify processed products. From an environmental perspective, the use of modern tools promotes water and fertilizer efficiency, though proper waste management remains necessary to avoid ecological risks. This study also underscores the need for local policy support in the form of financing facilitation, technology training, and access to agricultural tools to strengthen this participatory communication model. From an environmental perspective, the use of modern tools promotes water and fertilizer efficiency, though proper waste management remains necessary to avoid ecological risks. This study also underscores the need for local policy support in the form of financing facilitation, technology training, and access to agricultural tools to strengthen this participatory communication model.